Entrepreneurial capital leveraging innovation in micro firms: A mixed-methods perspective - Crespo, Nuno Fernandes (2021)
This study examines whether intangible resources such as entrepreneurial capital and collecting and donating knowledge contribute to building the absorptive capacity of micro firms to achieve innovation. The study adopts a mixed-methods approach that follows a complementary explanatory design strategy that uses a dataset of 228 micro firms from Brazil. The main findings are that knowledge sharing collection influences absorptive capacity; knowledge sharing collection has a partial mediator role between entrepreneurial capital and absorptive capacity; entrepreneurial capital, knowledge sharing collection, and absorptive capacity contribute to innovation; and knowledge sharing collection influences knowledge sharing donation. The theoretical contributions are the expansion of the view on antecedents of absorptive capacity and innovation in micro firms. The study also has managerial consequences by disclosing the contribution of intangible resources to innovation. Additionally, the study presents the alternative configurations that managers can choose to implement in order to reach absorptive capability and innovation.